Inhibition of veratridine-induced delayed inactivation of the voltage-sensitive sodium channel by synthetic analogs of crambescin B. Issue 5 (1st March 2017) - Tsukamoto, Tadaaki; Chiba, Yukie; Nakazaki, Atsuo; Ishikawa, Yuki; Nakane, Yoshiki; Cho, Yuko; Yotsu-Yamashita, Mari; Nishikawa, Toshio; Wakamori, Minoru; Konoki, Keiichi
Graphical abstract: Highlights: Crambescin B analogs do not inhibit VSSC. Crambescin B analogs inhibit veratridine-modified VSSC. Crambescin B analogs and local anesthetics may exhibit a similar mode of action. Abstract: Crambescin B carboxylic acid, a synthetic analog of crambescin B, was recently found to inhibit the voltage-sensitive sodium channels (VSSC) in a cell-based assay using neuroblastoma Neuro 2A cells. In the present study, whole-cell patch-clamp recordings were conducted with three heterologously expressed VSSC subtypes, Nav 1.2, Nav 1.6 and Nav 1.7, in a human embryonic kidney cell line HEK293T to further characterize the inhibition of VSSC by crambescin B carboxylic acid. Contrary to the previous observation, crambescin B carboxylic acid did not inhibit peak current evoked by depolarization from the holding potential of −100 mV to the test potential of −10 mV in the absence or presence of veratridine (VTD). In the presence of VTD, however, crambescin B carboxylic acid diminished VTD-induced sustained and tail currents through the three VSSC subtypes in a dose-dependent manner, whereas TTX inhibited both the peak current and the VTD-induced sustained and tail currents through all subtypes of VSSC tested. We thus concluded that crambescin B carboxylic acid does not block VSSC in a similar manner to TTX but modulate the action of VTD, thereby causing an apparent block of VSSC in the cell-based assay.